Bioactives from Artemisia dracunculus L. Enhance Insulin Sensitivity via Modulation of Skeletal Muscle Protein Phosphorylation - Kheterpal, Indu (Nutrition, 2014)
A botanical extract from Artemisia dracunculus L., termed PMI 5011, has been shown previously to improve insulin sensitivity by increasing cellular insulin signaling in in vitro and in vivo studies. These studies suggest that PMI 5011 effects changes in phosphorylation levels of proteins involved in insulin signaling. To explore effects of this promising botanical extract on the human skeletal muscle phosphoproteome, changes in site-specific protein phosphorylation levels in primary skeletal muscle cultures from obese, insulin resistant individuals were evaluated with and without insulin stimulation. Insulin resistance is a condition in which a normal or elevated insulin level results in an abnormal biologic response, e.g., glucose uptake. Using isobaric tagging for relative and absolute quantification (iTRAQ™) followed by phosphopeptide enrichment and liquid chromatography – tandem mass spectrometry, 125 unique phosphopeptides and 159 unique phosphorylation sites from 80 unique proteins were identified and quantified. Insulin stimulation of primary cultured muscle cells from insulin resistant individuals resulted in minimal increase in phosphorylation, demonstrating impaired insulin action in this condition. Treatment with PMI 5011 resulted in significant up regulation of 35 phosphopeptides that were mapped to proteins participating in the regulation of transcription, translation, actin cytoskeleton signaling, caveolae translocation and GLUT4 transport. These data further showed that PMI 5011 increased phosphorylation levels of specific amino acids in proteins in the insulin resistant state that are normally phosphorylated by insulin (thus, increasing cellular insulin signaling) and PMI 5011 also increased the abundance of phosphorylation sites of proteins regulating anti-apoptotic effects. Thus, the phosphoproteomics analysis demonstrated conclusively that PMI 5011 effects changes in phosphorylation levels of proteins and identified novel pathways by which PMI 5011 exerts its insulin sensitizing effects in skeletal muscle.